2017
DOI: 10.1007/s10728-017-0344-8
|View full text |Cite
|
Sign up to set email alerts
|

Are Concerns About Irremediableness, Vulnerability, or Competence Sufficient to Justify Excluding All Psychiatric Patients from Medical Aid in Dying?

Abstract: Some jurisdictions that have decriminalized assisted dying (like Canada) exclude psychiatric patients on the grounds that their condition cannot be determined to be irremediable, that they are vulnerable and in need of protection, or that they cannot be determined to be competent. We review each of these claims and find that none have been sufficiently well-supported to justify the differential treatment psychiatric patients experience with respect to assisted dying. We find bans on psychiatric patients' acces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 27 publications
0
40
2
Order By: Relevance
“…Rooney et al argue that irremediability can be predicted for individual depressed patients with help of staging models. 36 A questionnaire in 2016 among 248 Dutch psychiatrists found that 70% disagreed with the statement that it is impossible to assess whether a psychiatric patient suffers irremediably and unbearably, 12% agreed with this statement, and 17% was neutral. 50 In the ethical debate, however, many authors argue that it is impossible to reliably differentiate between patients who have a chance of recovery and those who do not.…”
Section: Arguments Concerning Uncertainty Of Diagnosis and Prognosismentioning
confidence: 99%
See 3 more Smart Citations
“…Rooney et al argue that irremediability can be predicted for individual depressed patients with help of staging models. 36 A questionnaire in 2016 among 248 Dutch psychiatrists found that 70% disagreed with the statement that it is impossible to assess whether a psychiatric patient suffers irremediably and unbearably, 12% agreed with this statement, and 17% was neutral. 50 In the ethical debate, however, many authors argue that it is impossible to reliably differentiate between patients who have a chance of recovery and those who do not.…”
Section: Arguments Concerning Uncertainty Of Diagnosis and Prognosismentioning
confidence: 99%
“…(2) Because of the episodic nature of some mental illnesses, a 1-year waiting period should be considered in the case of mental illness. Rooney et al 36 Case report (1) It is possible to determine whether psychiatric suffering is irremediable. 2The relative long survival of psychiatric patients who suffer irremediably makes exclusion from PAD especially harmful.…”
Section: Berghmans Andmentioning
confidence: 99%
See 2 more Smart Citations
“…These patients' potential entitlement, while beyond the scope of this paper, is important to consider and there has been extensive and continuing ethical discussion about who ought to be eligible for voluntary assisted dying (e.g. [18][19][20][21][22]). However, our focus in this paper is not on equal access in the sense of the justifiability of the Victorian eligibility criteria.…”
Section: Introductionmentioning
confidence: 99%